Generation Dependent Effects and Entrance to Mitochondria of Hybrid Dendrimers on Normal and Cancer Neuronal Cells In Vitro - Szwed, Aleksandra (Biomolecules, 2020)
Dendrimers as drug carriers can be utilized for drugs and siRNA delivery in central nervous system (CNS) disorders, including various types of cancers, such as neuroblastomas and gliomas. They have also been considered as drugs per se, for example as anti-Alzheimer’s disease (AD), anti-cancer, anti-prion or anti-inflammatory agents. Since the influence of carbosilane–viologen–phosphorus dendrimers (SMT1 and SMT2) on the basic cellular processes of nerve cells had not been investigated, we examined the impact of two generations of these hybrid macromolecules on two murine cell lines—cancer cell line N2a (mouse neuroblastoma) and normal immortalized cell line mHippoE-18 (embryonic mouse hippocampal cell line). We examined alterations in cellular responses including the activity of mitochondrial dehydrogenases, the generation of reactive oxygen species (ROS), changes in mitochondrial membrane potential, and morphological modifications and fractions of apoptotic and dead cells. Our results show that both dendrimers at low concentrations affected the cancer cell line more than the normal one. Also, generation-dependent effects were found: the highest generation induced greater cytotoxic effects and morphological modifications. The most promising is that the changes in mitochondrial membrane potential and transmission electron microscopy (TEM) images indicate that dendrimer SMT1 can reach mitochondria. Thus, SMT1 and SMT2 seem to have potential as nanocarriers to mitochondria or anti-cancer drugs per se in CNS disorders.